The Application of Experiential Teaching in Music Education in Secondary Vocational Schools - Hu, Dongni (Journal of Theory and Practice of Contemporary Education, 2023)
Music education in secondary vocational schools plays a very important role in improving students' artistic accomplishment and comprehensive quality. The experiential teaching mode should be actively applied in music teaching in secondary vocational schools, so that students can master more knowledge and skills, and constantly enhance their music appreciation ability. This paper mainly analyzes the application of experiential teaching in music education in secondary vocational schools for reference. Music experience is actually an experiential activity, and it is also an important way for teachers and students to communicate effectively. The teacher can reasonably design the teaching situation according to the students' actual situation and the basic objectives and requirements of teaching, and also arrange the tasks related to the teaching content, so as to improve the students' learning enthusiasm, lead the students to know, feel and understand music, and students can also express their understanding of music, and then cultivate their music literacy. Or teachers can give students some guidance in teaching, comprehensively summarize the teaching content, and evaluate the whole learning process of students, so as to mobilize students' learning enthusiasm.